2018
DOI: 10.1007/s13201-018-0646-5
|View full text |Cite
|
Sign up to set email alerts
|

Drainage morphometric analysis for assessing form and processes of the watersheds of Pachamalai hills and its adjoinings, Central Tamil Nadu, India

Abstract: The present study attempts to understand the form and geomorphic/hydrologic processes of the 20 watersheds of the Pachamalai hills and its adjoinings located in Tamil Nadu State of southern India from the analysis of its drainage morphometric characteristics. Survey of India's topographic sheets of 1:50,000 is the data source from which stream networks and watersheds of the study area were demarcated followed by the analysis of their morphometric characteristics using ArcGIS software. The results of the analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(15 citation statements)
references
References 34 publications
1
13
0
1
Order By: Relevance
“…This means that the number of streams usually decreases in geometric progression as the stream order increases (Horton 1945). This confirms the findings of Pophare and Balpande (2014) that the difference in rock structure is responsible for the different stream order. The 1st and 2nd stream orders, respectively, constitute 57.89% and 26.87% of the watershed originating from the mountains and hills with a steep/moderate slope and are usually seasonal.…”
Section: Stream Number (Nu)supporting
confidence: 91%
“…This means that the number of streams usually decreases in geometric progression as the stream order increases (Horton 1945). This confirms the findings of Pophare and Balpande (2014) that the difference in rock structure is responsible for the different stream order. The 1st and 2nd stream orders, respectively, constitute 57.89% and 26.87% of the watershed originating from the mountains and hills with a steep/moderate slope and are usually seasonal.…”
Section: Stream Number (Nu)supporting
confidence: 91%
“…To prioritize nine SW of BW, 3 significant morphometric variables (F s , L om and F f ) were considered. The cross-correlation between the 3 variables was performed as shown in Table 11 while CF was used as a factor to determine the priority rank (PR) of the 9 SW using Equation (19) as presented in Table 12. The calculation of the weight values assigned to each morphometric parameter was done by using the grand total of correlations to divide each variables' sum of correlation coefficient (Table 11).…”
Section: Weighted-sum Analysis Of Significant Morphometric Variablesmentioning
confidence: 99%
“…The authors suggested different thematic maps integrated with morphometric variables to determine the suitable areas for citing water and soil conservation measures. In India, several studies on watershed prioritization have been performed based on morphometric analysis using the potential of RS and GIS techniques [15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…We attribute these to the variations in the wetland microtopographic characteristics such as depth, width, and crosssectional area in the sampling stations across the wetland. Several other studies have also inferred that the topographic characteristics of aquatic ecosystems are among the significant determinants of flow variation (Wetzel 2001;Camila de Sousa et al 2011;Yunus et al 2003;Singh et al 2014;Pandi et al 2017;Soni 2017;Prabhakaran and Raj 2018), which in turn create heterogeneous micro-environments within wetlands.…”
Section: Discussionmentioning
confidence: 96%